Human resource development practices for proactive parenting: Navigating the challenges through A-M-O model - Osolase, Ehikioya Hilary; Mohd Rasdi, Roziah; Mansor, Zuraina; Janodi, Mohd Razaie; Hamsar, Mohd Nurhadi; Lukhman, Arief Aiman; Ijod, Giroon (Knowledge Words Publications, 2023)
A family unit is like an organization. The proactive role played by Human Resource Development in an organization, is synonymous to that of parenting in a family unit. In other words, proactive parenting plays the significant role of Human Resource Development in a family unit. Ineffective parenthood sometimes leads to ineffective offspring, which is similar to unproductive employees been unable to help achieve performance in an organization. Deploying the constituent parts of A-M-O model which are abilities, motivation, and opportunities, HRD practices in the context of an organization, namely training and development, performance appraisals, and feedback mechanisms, are able to assist in bringing the needed transformation resulting to proactive parenting and wellorganized family units. These are enablers for workforce and organizational efficiency, in addition to the wellbeing of the larger society. Employing a narrative review, the study focuses and explains the role of HRD practices for proactive parenting, through its incorporation into the mechanisms of A-M-O model. Utilizing the A-M-O model and the three HRD activities investigated for the study, future studies can apply qualitative, quantitative, or mixed-method research on selected families of working parents. In deploying primary data, this can bring in different viewpoint and outcome, when compared to that of the present study.